The Impact of Teacher Competence on Inclusive Education: Moderating Role of Islamic Religious Education Understanding - Fatimah Warosari, Yuli; Nurhayati, Nurhayati; Mahanis, Juni; Alia, Nurain (Ta'dib, 2025)
Inclusive education ensures that children with special needs can fully participate in the learning process alongside their peers, thereby promoting educational equity and the fulfillment of their rights. This study investigates the impact of teacher competence on the implementation of inclusive education, with a specific emphasis on the moderating role of teachers’ understanding of Islamic Religious Education. Employing a mixed-methods approach, the study integrates quantitative and qualitative strategies to obtain robust and comprehensive insights. Data were collected through the distribution of structured questionnaires, in-depth interviews, and direct field observations. The analysis was conducted using SPSS to ensure statistical rigor and precision. The results reveal that teacher competence significantly enhances the effectiveness of inclusive education practices. Furthermore, teachers’ understanding of Islamic Religious Education positively moderates the relationship between teacher competence and inclusive education outcomes, thereby amplifying the role of teacher competence in fostering successful inclusive learning environments. These findings underscore the importance of integrating both professional competence and religious pedagogical understanding in advancing inclusive educational frameworks.